Household Instability and Unpredictable Earnings Hinder Coping in Households with Food Insecure Children. Issue 4 (1st October 2016) - Hanson, Karla L.; Connor, Leah; Olson, Christine M.; Mills, Gregory
ABSTRACT: This mixed-methods study explored the circumstances and coping strategies of households at risk of food insecurity among children. Quantitative analyses guided the selection of two samples of households: (1) at risk for food insecure children, yet children were food secure (n = 19) and (2) with food insecure children (n = 54). Qualitative interviews with parents revealed that households with food insecure children were complex and fluctuating in composition and had unpredictable earnings. Coping strategies were similar in both samples, except that households with at risk yet food secure children described home cooking, a household coping strategy that may be attributed to their stable household composition and resources.